PELANGGARAN IMPLIKATUR PERCAKAPAN DALAM HUMOR MINANG BASIGINYANG - Yulfi Zawarnis (Kantor Bahasa Lampung, 2018)
AbstractThis research is a qualitative research that aims to describe the form of conversational implicatur used in Minang humors contained in Minang song album